Contemporary Qur’anic Exegesis: Bridging Classical and Modern Approaches - Dr Adeeba Siddiqui (Journal of Religion and Society, 2025)
This study examines contemporary Qur’anic exegesis with a focus on bridging classical and modern interpretive approaches to foster balanced, authentic, and relevant understandings of the divine text. Through qualitative, comparative, and analytical hermeneutical analysis, the research surveys classical traditions rooted in transmitted reports and linguistic precision, alongside modern trends shaped by rationalism, scientific inquiry, and socio-political demands. Classical exegesis offers enduring strengths in authenticity, textual coherence, and preservation of meaning, yet reveals limitations in addressing issues like science, gender equity, and pluralism. Modern approaches encompassing thematic, scientific, literary, feminist, and contextual methodologies enhance relevance but risk subjectivity and deviation. Points of convergence, such as shared commitment to Qur’anic centrality, ethical objectives (maqāṣid al-sharī ‘ah), and linguistic integrity, enable integrative frameworks including maqāṣid-based exegesis and bounded contextual Ijtihad. Case applications to bioethics, environmental stewardship, and interfaith dialogue demonstrate practical viability, while guidelines emphasize authenticity, avoidance of eisegesis, and rigorous training. The study proposes that harmonizing classical fidelity with modern tools revitalizes tafsir, ensuring the Qur’an’s guidance illuminates contemporary challenges without compromising its timeless sanctity. Ultimately, integrative models empower exegetes to navigate global complexities, enriching Islamic discourse and promoting ethical renewal. Keywords: Qur’anic Exegesis, Classical Tafsir, Modern Hermeneutics, Maqāṣid Al-Sharī ‘Ah, Integrative Frameworks, Contextual Ijtihad